Efecto de las prácticas fitosanitarias sobre la sostenibilidad del cultivo de arroz (Oryza sativa L) en el cantón La Troncal año 2018 - Torres Sánchez, Sinthya Tatiana (2019)
The present work was designed to evaluate the effect of phytosanitary practices on the sustainability of rice cultivation in the canton of La Troncal. Considering as objectives: characterize phytosanitary activity, verify environmental sustainability indicators and the profitability of rice cultivation. The information was obtained through a structured survey applied to 63 farmers corresponding to a sample of a universe of 175 rice growers registered in the association of irrigation users Manuel de J Calle belonging to the canton La Troncal, province of Cañar. Obtaining as conclusions that training is needed to carry out phytosanitary practices since most of them currently do it with chemical pesticides, the indicators of environmental sustainability express that the rice activity is sustainable. At the same time the economic profitability is low with a RBC of 0.24. In order to improve phytosanitary practices, farmers must associate to receive training on environmentally sustainable techniques, lower input costs and obtain better markets to obtain a better sale price. Keywords: Agroecology, Rice, Phytosanity, Oryza sativa, Sustainability